e-Services (IntechOpen, 2023)
The turn of the new millennium has brought with it an explosion of activity around electronic services (e-services) in the form of e-commerce, e-business, e-government, e-learning, and so on. The provision of all possible goods and services electronically via the Internet with the use of semantic web technologies has seen a paradigm shift from the traditional brick-and-mortar location-based services to the ubiquitous provision of goods and services online. An understanding of this paradigm shift and the fundamental properties of e-service composition is required in order to take full advantage of the paradigm. As such, this book provides comprehensive coverage and understanding of the use of e-services within the technological, business, management, and organizational domains. Chapters cover such topics as digitized learning, information and communication technology in sports, cloud computing for universities, and more. This book is a reference book for scholars, researchers, and practitioners looking to update their knowledge on methodologies, theoretical analyses, modeling, simulation, and empirical studies on e-services.